PENGARUH SERTIFIKAT HALAL, VIRAL MARKETING, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MIXUE - Faiq, Muhammad Ammar; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2024)
The research is aimed at identifying and testing the influence of halal certificates, viral marketing, and brand image on consumer purchasing decisions of mixue products. This research uses a quantitative associative approach, utilizing primary data obtained through the distribution of questionnaires. The distribution of these questionnaires successfully obtained 123 respondents. The method of analysis used in the research is double linear regression. The results of the research showed that the variables of a valid certificate and brand image influenced the purchase decision of Mixue products. Meanwhile, viral marketing variables have no influence on Mixue product purchase decisions. Meanwhile, these three variables simultaneously influence consumer purchasing decisions of mixed products. Therefore, by taking into account factors such as halal certificates obtained through the process of MUI make consumers more and more confident in the validity of Mixue products, as well as viral marketing of the Mixue product through some influencers as also reviews from other consumers